Preparation method of hydrogel material scanning electron microscope sample

By employing swelling equilibrium pretreatment and freeze-drying methods, the structural deformation problem of hydrogels during scanning electron microscopy observation was solved, enabling high-fidelity microstructure observation of hydrogel samples.

CN121476264APending Publication Date: 2026-02-06EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511375213.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

The high water content of hydrogels leads to liquid nitrogen boiling contamination and structural deformation during scanning electron microscopy observation. Existing preparation methods are prone to causing pore collapse, surface wrinkles, and network breakage, affecting the accuracy of microstructure measurement.

Method used

A method combining swelling equilibrium pretreatment and freeze-drying was adopted. The hydrogel was first swollen in buffer solution until thermodynamic equilibrium was reached, and then freeze-dried to release internal stress through chain segment relaxation, thereby constructing a homogeneous network structure.

Benefits of technology

It effectively maintains the original morphology of the three-dimensional network structure of the hydrogel, reduces the structural irregular collapse caused by rapid dehydration, and provides more accurate support for microstructure observation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121476264A_ABST
    Figure CN121476264A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrogel material scanning electron microscope sample, which comprises the following steps: putting a hydrogel block in a PBS buffer solution for swelling, taking out the hydrogel block at set intervals, removing water on the surface of the hydrogel, weighing and recording until the weight of the hydrogel is not increased any more to achieve swelling equilibrium, removing the PBS buffer solution, adding ultrapure water, and standing to obtain the hydrogel material scanning electron microscope sample. Changing fresh ultrapure water once every a period of time, changing water for 2-4 times, taking out, freezing, and freeze-drying to obtain a freeze-dried sample; and fixing the freeze-dried sample, and plating a conductive material to obtain the conductive hydrogel material scanning electron microscope sample. The preparation method of the hydrogel material scanning electron microscope sample provided by the invention is simple and easy to operate and low in cost, the irregular structure collapse phenomenon caused by rapid dehydration of the hydrogel material is effectively reduced by introducing a swelling procedure, the original morphology of the three-dimensional network structure of the hydrogel freeze-dried sample can be well maintained, and the preparation method is suitable for industrial production. And an effective technical support is provided for related research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hydrogel material preparation, and more specifically, relates to a method for preparing scanning electron microscope (SEM) samples of hydrogel materials. Background Technology

[0002] Hydrogels are soft materials composed of hydrophilic polymer networks, possessing excellent biocompatibility and biomimetic properties, and are widely used in biomedicine, tissue engineering, flexible electronics, and other fields. Their microstructure (such as three-dimensional porosity, pore size distribution, and surface topology) directly affects material properties (such as mechanical strength, swelling behavior, and drug release efficiency). Scanning electron microscopy (SEM), due to its high resolution and intuitive morphological display capabilities, has become a key tool for revealing the microstructure of hydrogels. However, the high water content of hydrogels (typically exceeding 90%) presents significant challenges for SEM observation: direct observation in the hydrated state can lead to liquid nitrogen boiling contamination in the vacuum chamber, while traditional sample preparation methods are prone to structural deformation or even damage.

[0003] The current standard SEM sample preparation process mainly includes dehydration, freeze-drying, and gold sputtering. The dehydration process of hydrogels requires rapid removal of water to prevent ice crystal formation, often using liquid nitrogen quenching or freezing at -20°C followed by freeze-drying. However, direct drying can easily lead to drastic volume shrinkage due to the instantaneous evaporation of water, resulting in structural distortions such as pore collapse, surface wrinkles, and network breakage. This deformation can obscure the true three-dimensional topological characteristics of the hydrogel, leading to inaccurate measurements of key parameters such as porosity and pore size distribution. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing scanning electron microscope (SEM) samples of hydrogel materials.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] In a first aspect, the present invention provides a method for preparing a scanning electron microscope (SEM) sample of a hydrogel material, comprising the following steps:

[0007] The hydrogel block is placed in PBS buffer to swell. The hydrogel block is removed every once in a while, the water on the surface of the hydrogel is removed, and the weight is weighed and recorded until the weight of the hydrogel no longer increases and the swelling equilibrium is reached. The PBS buffer is removed, ultrapure water is added, and fresh ultrapure water is changed every once in a while. The water is changed 2 to 4 times (preferably 3 times). The sample is then taken out, frozen, and lyophilized to obtain the lyophilized sample.

[0008] The freeze-dried sample was fixed and coated with a conductive material to obtain a conductive hydrogel material scanning electron microscope sample.

[0009] The hydrogel is selected from gelatin-based hydrogels, hyaluronic acid hydrogels, and alginate hydrogels.

[0010] The gelatin-based hydrogel is selected from gelatin-based hydrogels based on dynamic chemical bonds and gelatin-based hydrogels based on non-dynamic covalent bonds.

[0011] The preparation method of the gelatin-based hydrogel based on dynamic chemical bonds includes the following steps:

[0012] A polyvinyl alcohol aqueous solution with a solid content of 1-10% (preferably 2%, 5%, or 10%) and a phenylboronic acid-modified gelatin aqueous solution with a solid content of 1-10% (preferably 2%, 5%, or 10%) were mixed by vortexing (1000 rpm, 10 min) to obtain a gelatin-based hydrogel with a solid content of 1-10% (preferably 2%, 5%, or 10%) based on dynamic chemical bonds.

[0013] The method for preparing the polyvinyl alcohol aqueous solution with a solid content of 1-10% (preferably 2%, 5%, or 10%) includes the following steps: dissolving polyvinyl alcohol in ultrapure water to obtain a polyvinyl alcohol aqueous solution with a solid content of 1-10% (preferably 2%, 5%, or 10%).

[0014] The method for preparing the phenylboronic acid-modified gelatin aqueous solution with a solid content of 1-10% (preferably 2%, 5%, or 10%) includes the following steps: dissolving phenylboronic acid-modified gelatin in ultrapure water to obtain a phenylboronic acid-modified gelatin aqueous solution with a solid content of 1-10% (preferably 2%, 5%, or 10%).

[0015] The preparation method of the phenylboronic acid modified gelatin includes the following steps:

[0016] Type A gelatin is dissolved in ultrapure water at a temperature of 50-60℃ (preferably 55℃). 3-Aminophenylboronic acid is added to the system and stirred continuously until dissolution is complete. EDC·HCl and NHS are added sequentially. 1M hydrochloric acid aqueous solution is added to adjust the pH of the reaction system to 5-6 (preferably 5.5). The mass ratio of type A gelatin, 3-aminophenylboronic acid, EDC·HCl, and NHS is 1:1-3:0.01-1:0.05-1 (preferably 1:1.25:0.2:0.125). The reaction solution is continuously magnetically stirred at a temperature of 50-60℃ (preferably 55℃) for 1-24 hours (preferably 24 hours). After the reaction is completed, the reaction solution is transferred to a dialysis bag (molecular weight cutoff of 14000 Da) and dialyzed with ultrapure water for 3-6 days (preferably 5 days). The solution is then freeze-dried (-80℃, 3 days) to obtain the phenylboronic acid-modified gelatin.

[0017] The method for preparing the gelatin-based hydrogel based on non-dynamic covalent bonds includes the following steps:

[0018] A phenyl (2,4,6-trimethylbenzoyl)lithium phosphate aqueous solution with a solid content of 0.05~0.5% (preferably 0.1%) and a methacrylated gelatin aqueous solution with a solid content of 1~40% (preferably 20%) are vortexed and mixed to obtain a gelatin-based hydrogel with a solid content of 1~10% (preferably 5% or 10%).

[0019] The method for preparing the aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate with a solid content of 0.05~0.5% (preferably 0.1%) includes the following steps: dissolving lithium phenyl (2,4,6-trimethylbenzoyl)phosphate (LAP) in ultrapure water to obtain an aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate with a solid content of 0.05~0.5% (preferably 0.1%).

[0020] The method for preparing the methacrylamide gelatin aqueous solution with a solid content of 1-40% (preferably 20%) includes the following steps: dissolving methacrylamide type A gelatin in ultrapure water to obtain a methacrylamide gelatin aqueous solution with a solid content of 1-40% (preferably 20%).

[0021] The preparation method of the methacrylated type A gelatin includes the following steps:

[0022] Type A gelatin was added to a PBS (pH=7.4) solution and stirred at 45-55°C (preferably 50°C) until completely dissolved. Methacrylic anhydride was added dropwise to the reaction solution and reacted in the dark for 2-4 hours (preferably 3 hours). The mass ratio of type A gelatin to methacrylic anhydride was 1-10:1 (preferably 2:1). The reaction was stopped by adding PBS solution. The mixture was dialyzed in deionized water for 2-4 days (preferably 3 days, MWCO=14000 Da) and then lyophilized (at -80°C, under vacuum of 5 Pa) to obtain the methacrylated type A gelatin.

[0023] The PBS buffer solution has a pH of 7.4 and a temperature of 37°C.

[0024] The time interval for removing the hydrogel block is 0.5 to 2 hours (preferably 1 hour).

[0025] The interval for replacing the ultrapure water with fresh water is 1 to 10 minutes (preferably 5 minutes).

[0026] The freezing conditions are: freezing at a temperature of -18 to -25°C (preferably -20°C) for 1 to 3 days (preferably 2 days), or direct liquid nitrogen quenching.

[0027] The freeze-drying conditions are as follows: freeze-drying at a temperature of -60 to -80°C (preferably -70°C) for 2 to 5 days (preferably 4 days), and a vacuum environment of 1 to 10 Pa (preferably 5 Pa).

[0028] The freeze-dried sample is fixed by using conductive adhesive.

[0029] The conductive material being plated is either gold or carbon, with gold plating being preferred.

[0030] By adopting the above technical solution, the present invention has the following advantages and beneficial effects:

[0031] The method for preparing hydrogel material scanning electron microscope samples provided by this invention is simple, easy to operate, and low in cost. By introducing a swelling procedure, it effectively reduces the structural irregularity and collapse caused by rapid dehydration of hydrogel materials, and can better maintain the original morphology of the three-dimensional network structure of the freeze-dried hydrogel sample, providing effective technical support for related research.

[0032] The method for preparing hydrogel material scanning electron microscope samples provided by the present invention produces samples with good morphology retention. This method effectively maintains the original morphology of the three-dimensional network structure of the hydrogel through a process of swelling equilibrium followed by freeze-drying.

[0033] The preparation method of this invention is based on a freeze-drying strategy using swelling equilibrium pretreatment. Its core lies in: pre-swelling the hydrogel to a thermodynamic equilibrium state before freeze-drying, releasing internal stress through chain segment relaxation, and constructing a more homogeneous network structure. The swell-equilibrium hydrogel can suppress micro-region collapse caused by localized stress concentration during vacuum freeze-drying. Swelling the hydrogel before freeze-drying effectively solves the problem of preparing hydrogel scanning electron microscopy samples. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the structure of a scanning electron microscope sample of a gelatin-based hydrogel with a solid content of 2% based on dynamic chemical bonds, obtained by swelling treatment.

[0035] Figure 2 This is a schematic diagram of the structure of a scanning electron microscope sample of a gelatin-based hydrogel with a solid content of 5% based on dynamic chemical bonds, obtained by swelling treatment.

[0036] Figure 3 This is a schematic diagram of the structure of a scanning electron microscope sample of a gelatin-based hydrogel with a solid content of 10% based on dynamic chemical bonds, obtained by swelling treatment.

[0037] Figure 4 This is a schematic diagram of the structure of a scanning electron microscope sample of a gelatin-based hydrogel with a solid content of 5% and based on non-dynamic covalent bonds, obtained by swelling treatment.

[0038] Figure 5 This is a schematic diagram of the structure of a scanning electron microscope sample of a gelatin-based hydrogel with a solid content of 10% and based on non-dynamic covalent bonds, obtained by swelling treatment.

[0039] Figure 6 This is a schematic diagram of the structure of a gelatin-based hydrogel with a solid content of 5% after direct freeze-drying.

[0040] Figure 7 This is a schematic diagram of the structure of a gelatin-based hydrogel with a solid content of 5% after direct freeze-drying. Detailed Implementation

[0041] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments, further clarifies the invention. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive, and should not be construed as limiting the scope of protection of the present invention.

[0042] Example 1

[0043] A method for preparing a scanning electron microscope (SEM) sample of a hydrogel material includes the following steps:

[0044] Polyvinyl alcohol was dissolved in ultrapure water to obtain a polyvinyl alcohol aqueous solution with a solid content of 2%.

[0045] The preparation method of phenylboronic acid modified gelatin includes the following steps:

[0046] 4 g of type A gelatin (Gel, Bloom value 221 g, CAS No.: 9000-70-8, purchased from Shanghai Naicheng Biotechnology Co., Ltd.) was dissolved in 200 mL of ultrapure water under constant temperature stirring at 55℃. After complete dissolution, 5 g of 3-aminophenylboronic acid (98%, CAS No.: 30418-59-8, purchased from Shanghai Xinbo Chemical Technology Co., Ltd.) was added to the system, and stirring was continued until complete dissolution. 0.8 g of EDC·HCl and 0.5 g of NHS were added sequentially, and 1 M hydrochloric acid aqueous solution was added to adjust the pH of the reaction system to approximately 5.5. The reaction solution was continuously magnetically stirred at 55℃ for 24 h. After the reaction, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 14000 Da, dialyzed with ultrapure water for 5 days, and freeze-dried (-80 ℃, 3 days) to obtain 7.49 g of phenylboronic acid-modified gelatin.

[0047] The gelatin modified with phenylboronic acid was dissolved in ultrapure water to obtain an aqueous solution of gelatin modified with phenylboronic acid with a solid content of 2%.

[0048] 50 mL of a 2% solids content polyvinyl alcohol (type 1799, CAS No.: 9002-89-5, purchased from Shanghai Naicheng Biotechnology Co., Ltd.) aqueous solution and 50 mL of a 2% solids content phenylboronic acid modified gelatin aqueous solution were vortexed (1000 rpm) for 10 min to obtain a 2% solids content gelatin-based hydrogel based on dynamic chemical bonds.

[0049] Calculation of solid content:

[0050] Solid content of hydrogel (%) = (m1 / m) × 100%

[0051] Where m is the mass of the hydrogel, and m1 is the mass of the hydrogel after freeze-drying.

[0052] The prepared gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) based on dynamic chemical bonds was placed in 100 mL of PBS buffer (pH=7.4, 37℃) to swell. Every 1 hour, the hydrogel block was removed, and the water on the surface was carefully absorbed with filter paper. The weight was weighed and recorded until the weight of the hydrogel no longer increased, reaching swelling equilibrium. The PBS buffer was removed, and ultrapure water was added. Fresh ultrapure water was added every 5 minutes, for a total of 3 water changes. The sample was then placed in a freezer at -20℃ for 2 days and freeze-dried for 4 days using a vacuum freeze dryer (at -70℃, vacuum environment: 5 Pa) to obtain the freeze-dried sample. The freeze-dried sample was fixed on the sample stage using conductive adhesive (model: SPI#05081-AB, purchased from Zhongjing Scientific Instruments Technology Co., Ltd.), and gold was deposited on the surface of the freeze-dried sample using a magnetron sputtering coating instrument (target: Au, sputtering current: 20 mA) to obtain a conductive hydrogel material for scanning electron microscopy.

[0053] The prepared hydrogel material samples were imaged using a scanning electron microscope (SEM) to observe the topological network structure of the hydrogel material samples. The results are as follows: Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of a scanning electron microscope (SEM) sample of a gelatin-based hydrogel with a solid content of 2% based on dynamic chemical bonds, obtained by swelling treatment (scale bar: 100 μm). As can be seen from the figure, the structure of the hydrogel sample is an interconnected and uniform porous structure, indicating that the prepared hydrogel sample retains the original morphology of the three-dimensional network of the hydrogel well.

[0054] Example 2

[0055] A method for preparing a scanning electron microscope (SEM) sample of a hydrogel material includes the following steps:

[0056] Polyvinyl alcohol was dissolved in ultrapure water to obtain a polyvinyl alcohol aqueous solution with a solid content of 5%.

[0057] The gelatin modified with phenylboronic acid was dissolved in ultrapure water to obtain an aqueous solution of gelatin modified with phenylboronic acid with a solid content of 5%.

[0058] 50 mL of a 5% polyvinyl alcohol aqueous solution and 50 mL of a 5% phenylboronic acid-modified gelatin aqueous solution were vortexed (1000 rpm) for 10 min to obtain a gelatin-based hydrogel with a 5% solid content based on dynamic chemical bonds.

[0059] The prepared gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) based on dynamic chemical bonds was placed in 100 mL of PBS buffer (pH=7.4, 37℃) to swell. Every 1 hour, the hydrogel block was removed, and the water on the surface was carefully absorbed with filter paper. The weight was weighed and recorded until the weight of the hydrogel no longer increased, reaching swelling equilibrium. The PBS buffer was removed, and ultrapure water was added. Fresh ultrapure water was added every 5 minutes, for a total of 3 water changes. The sample was then placed in a freezer at -20℃ for 2 days and freeze-dried for 4 days using a vacuum freeze dryer (at -70℃, vacuum environment: 5 Pa) to obtain the freeze-dried sample. The freeze-dried sample was fixed on the sample stage using conductive adhesive (model: SPI#05081-AB, purchased from Zhongjing Scientific Instruments Technology Co., Ltd.), and gold was deposited on the surface of the freeze-dried sample using a magnetron sputtering coating instrument (target: Au, sputtering current: 20 mA) to obtain a conductive hydrogel material for scanning electron microscopy.

[0060] The prepared hydrogel material samples were imaged using a scanning electron microscope (SEM) to observe the internal topological network structure. The results are as follows: Figure 2 As shown, Figure 2 This is a schematic diagram of the structure of a scanning electron microscope (SEM) sample of a gelatin-based hydrogel with a solid content of 5% based on dynamic chemical bonds, obtained by swelling treatment (scale bar: 100 μm). As can be seen from the figure, the structure of the hydrogel sample is an interconnected and uniform porous structure, indicating that the prepared hydrogel sample retains the original morphology of the three-dimensional network of the hydrogel well.

[0061] Example 3

[0062] A method for preparing a scanning electron microscope (SEM) sample of a hydrogel material includes the following steps:

[0063] Polyvinyl alcohol was dissolved in ultrapure water to obtain a polyvinyl alcohol aqueous solution with a solid content of 10%.

[0064] The gelatin modified with phenylboronic acid was dissolved in ultrapure water to obtain an aqueous solution of gelatin modified with phenylboronic acid with a solid content of 10%.

[0065] 50 mL of a 10% solids-content polyvinyl alcohol aqueous solution and 50 mL of a 10% solids-content phenylboronic acid-modified gelatin aqueous solution were vortexed (1000 rpm) for 10 min to obtain a 10% solids-content gelatin-based hydrogel based on dynamic chemical bonds.

[0066] The prepared gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) based on dynamic chemical bonds was placed in 100 mL of PBS buffer (pH=7.4, 37℃) to swell. Every 1 hour, the hydrogel block was removed, and the water on the surface was carefully absorbed with filter paper. The weight was weighed and recorded until the weight of the hydrogel no longer increased, reaching swelling equilibrium. The PBS buffer was removed, and ultrapure water was added. Fresh ultrapure water was added every 5 minutes, for a total of 3 water changes. The sample was then placed in a freezer at -20℃ for 2 days and freeze-dried for 4 days using a vacuum freeze dryer (at -70℃, vacuum environment: 5 Pa) to obtain the freeze-dried sample. The freeze-dried sample was fixed on the sample stage using conductive adhesive (model: SPI#05081-AB, purchased from Zhongjing Scientific Instruments Technology Co., Ltd.), and gold was deposited on the surface of the freeze-dried sample using a magnetron sputtering coating instrument (target: Au, sputtering current: 20 mA) to obtain a conductive hydrogel material for scanning electron microscopy.

[0067] The prepared hydrogel material was imaged using a scanning electron microscope (SEM) to observe its internal three-dimensional network structure. The results are as follows: Figure 3 As shown, Figure 3 This is a schematic diagram of the structure of a scanning electron microscope (SEM) sample of a gelatin-based hydrogel with a solid content of 10% based on dynamic chemical bonds, obtained by swelling treatment (scale bar: 100 μm). As can be seen from the figure, the structure of the hydrogel sample is an interconnected and uniform porous structure, indicating that the prepared hydrogel sample retains the original morphology of the three-dimensional network of the hydrogel well.

[0068] Example 4

[0069] A method for preparing a scanning electron microscope (SEM) sample of a hydrogel material includes the following steps:

[0070] Lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) was dissolved in ultrapure water to obtain an aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate with a solid content of 0.1%.

[0071] The preparation method of methacrylamide-modified type A gelatin (GelMA) includes the following steps: 10 g of type A gelatin is added to 100 mL of PBS (pH=7.4) solution and stirred in a constant temperature oil bath at 50 ℃ until completely dissolved. 5 g of methacrylic anhydride is added dropwise to the reaction solution and reacted in the dark for 3 h. The reaction is stopped by adding 100 mL of PBS solution. The mixture is dialyzed in deionized water for 3 days (MWCO=14000 Da) and lyophilized (at -80 ℃, under vacuum: 5 Pa) to obtain 14.15 g of methacrylamide-modified type A gelatin (GelMA).

[0072] Methacrylated type A gelatin was dissolved in ultrapure water to obtain an aqueous solution of methacrylated gelatin with a solid content of 10%.

[0073] A 0.1% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate aqueous solution and a 10% methacrylated gelatin aqueous solution were vortexed (1000 rpm) for 10 min to obtain a gelatin-based hydrogel with a 5% solid content based on non-dynamic covalent bonds.

[0074] The prepared gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) based on non-dynamic covalent bonds was placed in 100 mL of PBS buffer (pH=7.4, 37℃) to swell. Every 1 hour, the hydrogel block was removed, and the water on the surface was carefully absorbed with filter paper. The weight was weighed and recorded until the weight of the hydrogel no longer increased, reaching swelling equilibrium. The PBS buffer was removed, and ultrapure water was added. Fresh ultrapure water was added every 5 minutes, for a total of 3 water changes. The sample was then placed in a freezer at -20℃ for 2 days and freeze-dried for 4 days using a vacuum freeze dryer (at -70℃, vacuum environment: 5 Pa) to obtain the freeze-dried sample. The freeze-dried sample was fixed on the sample stage using conductive adhesive (model: SPI#05081-AB, purchased from Zhongjing Scientific Instruments Technology Co., Ltd.), and gold was deposited on the surface of the freeze-dried sample using a magnetron sputtering coating instrument (target: Au, sputtering current: 20 mA) to obtain a conductive hydrogel material for scanning electron microscopy.

[0075] The prepared hydrogel material samples were imaged using a scanning electron microscope (SEM) to observe the internal topological network structure. The results are as follows: Figure 4 As shown, Figure 4This is a schematic diagram of the structure of a scanning electron microscope (SEM) sample of a gelatin-based hydrogel with a solid content of 5% based on non-dynamic covalent bonds, obtained by swelling treatment (scale bar: 100 μm). As can be seen from the figure, the structure of the hydrogel sample is an interconnected, complete, and uniform porous structure, indicating that the prepared hydrogel sample has good morphology retention.

[0076] Example 5

[0077] A method for preparing a scanning electron microscope (SEM) sample of a hydrogel material includes the following steps:

[0078] Lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) was dissolved in ultrapure water to obtain an aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate with a solid content of 0.1%.

[0079] Methacrylated type A gelatin was dissolved in ultrapure water to obtain an aqueous solution of methacrylated gelatin with a solid content of 20%.

[0080] 50 mL of a 0.1% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate aqueous solution and 50 mL of a 20% methacrylated gelatin aqueous solution were vortexed (1000 rpm) for 10 min to obtain a gelatin-based hydrogel with a 10% solid content based on non-dynamic covalent bonds.

[0081] The prepared gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) based on non-dynamic covalent bonds was placed in 100 mL of PBS buffer (pH=7.4, 37℃) to swell. Every 1 hour, the hydrogel block was removed, and the water on the surface was carefully absorbed with filter paper. The weight was weighed and recorded until the weight of the hydrogel no longer increased, reaching swelling equilibrium. The PBS buffer was removed, and ultrapure water was added. Fresh ultrapure water was added every 5 minutes, for a total of 3 water changes. The sample was then placed in a freezer at -20℃ for 2 days and freeze-dried for 4 days using a vacuum freeze dryer (at -70℃, vacuum environment: 5 Pa) to obtain the freeze-dried sample. The freeze-dried sample was fixed on the sample stage using conductive adhesive (model: SPI#05081-AB, purchased from Zhongjing Scientific Instruments Technology Co., Ltd.), and gold was deposited on the surface of the freeze-dried sample using a magnetron sputtering coating instrument (target: Au, sputtering current: 20 mA) to obtain a conductive hydrogel material for scanning electron microscopy.

[0082] The prepared hydrogel material was imaged using a scanning electron microscope (SEM) to observe the internal topological network morphology of the SEM sample. The results are as follows: Figure 5 As shown, Figure 5This is a schematic diagram of the structure of a scanning electron microscope (SEM) sample of a gelatin-based hydrogel with a solid content of 10% based on non-dynamic covalent bonds, obtained by swelling treatment (scale bar: 100 μm). As can be seen from the figure, the structure of the hydrogel sample is an interconnected, complete, and uniform porous structure, indicating that the prepared hydrogel sample has good morphology retention.

[0083] Comparative Example 1

[0084] The gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) with a solid content of 5% based on dynamic chemical bonds prepared in Example 2 was frozen in a refrigerator at -20°C for 2 days and then freeze-dried in a vacuum freeze dryer for 4 days (at -70°C and in a vacuum environment of 5 Pa). The freeze-dried sample was fixed on the sample stage with conductive adhesive, and gold was deposited on the surface of the freeze-dried sample by magnetron sputtering (target: Au, sputtering current: 20 mA) to obtain a scanning electron microscope sample of conductive hydrogel material.

[0085] The prepared hydrogel material was imaged using a scanning electron microscope (SEM) to observe its internal three-dimensional network structure. The results are as follows: Figure 6 As shown, Figure 6 This is a schematic diagram of the structure of a gelatin-based hydrogel with a solid content of 5% after direct freeze-drying (scale bar: 100 μm). As can be seen from the figure, compared with the hydrogel material SEM sample prepared in Example 2, the hydrogel material SEM sample prepared in Comparative Example 1 exhibits obvious surface wrinkles and partial collapse, indicating that the sample structure has been damaged to some extent, which is not conducive to the observation of the hydrogel network structure.

[0086] Comparative Example 2

[0087] The gelatin-based hydrogel (rectangular, 3 cm long, 2 cm wide, and 1 cm high) prepared in Example 4 based on dynamic chemical bonds was frozen in a refrigerator at -20°C for 2 days and then freeze-dried in a vacuum freeze dryer for 4 days (at -70°C and in a vacuum environment of 5 Pa). The freeze-dried sample was fixed on the sample stage with conductive adhesive, and gold was deposited on the surface of the freeze-dried sample by magnetron sputtering (target: Au, sputtering current: 20 mA) to obtain a scanning electron microscope sample of conductive hydrogel material.

[0088] The prepared hydrogel material samples were imaged using a scanning electron microscope (SEM) to observe the internal topological network structure. The results are as follows: Figure 7 As shown, Figure 7This is a schematic diagram of the structure of a gelatin-based hydrogel with a solid content of 5% after direct freeze-drying (scale bar: 100 μm). As can be seen from the figure, compared with the hydrogel material prepared in Example 4, the hydrogel material prepared in Comparative Example 2 exhibits obvious surface wrinkles and partial collapse, indicating that the sample structure has been damaged to some extent, which is not conducive to the observation of the hydrogel network structure.

[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-described technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing scanning electron microscope (SEM) samples of hydrogel materials, characterized in that, Includes the following steps: The hydrogel block was placed in PBS buffer to swell. The hydrogel block was removed every once in a while, the water on the surface of the hydrogel was removed, and the weight was weighed and recorded until the weight of the hydrogel no longer increased and reached swelling equilibrium. The PBS buffer was removed, and ultrapure water was added. Fresh ultrapure water was added every once in a while. The water was changed 2 to 4 times. The sample was then taken out, frozen, and lyophilized to obtain the lyophilized sample. The freeze-dried sample was fixed and coated with a conductive material to obtain a conductive hydrogel material scanning electron microscope sample. The hydrogel is selected from gelatin-based hydrogel, hyaluronic acid hydrogel, and alginate hydrogel; The gelatin-based hydrogel is selected from gelatin-based hydrogels based on dynamic chemical bonds and gelatin-based hydrogels based on non-dynamic covalent bonds. The preparation method of the gelatin-based hydrogel based on dynamic chemical bonds includes the following steps: A polyvinyl alcohol aqueous solution with a solid content of 1-10% and a gelatin aqueous solution modified with phenylboronic acid with a solid content of 1-10% were mixed by vortexing to obtain a gelatin-based hydrogel with a solid content of 1-10% based on dynamic chemical bonds. The method for preparing the gelatin-based hydrogel based on non-dynamic covalent bonds includes the following steps: A 1:1 volume ratio of 0.05-0.5% phenyl (2,4,6-trimethylbenzoyl) lithium phosphate aqueous solution and 1-40% methacrylated gelatin aqueous solution were vortexed to obtain a gelatin-based hydrogel with a solid content of 1-10% based on non-dynamic covalent bonds.

2. The method for preparing scanning electron microscope samples of hydrogel materials according to claim 1, characterized in that, The method for preparing the polyvinyl alcohol aqueous solution with a solid content of 1-10% includes the following steps: dissolving polyvinyl alcohol in ultrapure water to obtain a polyvinyl alcohol aqueous solution with a solid content of 1-10%. The method for preparing the phenylboronic acid-modified gelatin aqueous solution with a solid content of 1-10% includes the following steps: dissolving phenylboronic acid-modified gelatin in ultrapure water to obtain a phenylboronic acid-modified gelatin aqueous solution with a solid content of 1-10%.

3. The method for preparing scanning electron microscope samples of hydrogel materials according to claim 2, characterized in that, The preparation method of the phenylboronic acid modified gelatin includes the following steps: Type A gelatin was dissolved in ultrapure water at a temperature of 50-60°C. 3-Aminophenylboronic acid was added to the system and stirred continuously until dissolution was complete. EDC·HCl and NHS were added sequentially, and hydrochloric acid aqueous solution was added to adjust the pH of the reaction system to 5-6. The mass ratio of type A gelatin, 3-aminophenylboronic acid, EDC·HCl, and NHS was 1:1-3:0.01-1:0.05-1. The reaction solution was continuously magnetically stirred at a temperature of 50-60°C for 1-24 hours. After the reaction was completed, the reaction solution was transferred to a dialysis bag and dialyzed with ultrapure water for 3-6 days. After freeze-drying, the phenylboronic acid-modified gelatin was obtained.

4. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 1, characterized in that, The method for preparing the aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate with a solid content of 0.05~0.5% includes the following steps: dissolving lithium phenyl (2,4,6-trimethylbenzoyl)phosphate salt in ultrapure water to obtain an aqueous solution of lithium phenyl (2,4,6-trimethylbenzoyl)phosphate with a solid content of 0.05~0.5%; The method for preparing the methacrylated gelatin aqueous solution with a solid content of 1-40% includes the following steps: dissolving methacrylated type A gelatin in ultrapure water to obtain a methacrylated gelatin aqueous solution with a solid content of 1-40%.

5. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 4, characterized in that, The preparation method of the methacrylated type A gelatin includes the following steps: Type A gelatin was added to PBS solution and stirred at 45-55°C until completely dissolved. Methacrylic anhydride was added dropwise to the reaction solution and reacted in the dark for 2-4 hours. The mass ratio of type A gelatin to methacrylic anhydride was 1-10:

1. The reaction was stopped by adding PBS solution. The mixture was dialyzed in deionized water for 2-4 days and then lyophilized to obtain the methacrylated type A gelatin.

6. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 1, characterized in that, The PBS buffer solution has the following pH values: 7.4, 37°C. The hydrogel block is removed at intervals of 0.5 to 2 hours.

7. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 1, characterized in that, The interval for changing the ultrapure water to fresh water is 1-10 minutes. The freezing conditions are: freezing at a temperature of -18 to -25°C for 1 to 3 days, or direct liquid nitrogen quenching.

8. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 1, characterized in that, The freeze-drying conditions are as follows: freeze-drying at a temperature of -60 to -80°C for 2 to 5 days, and in a vacuum environment of 1 to 10 Pa.

9. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 1, characterized in that, The freeze-dried sample is fixed by using conductive adhesive.

10. The method for preparing a scanning electron microscope sample of hydrogel material according to claim 1, characterized in that, The conductive material being plated is either gold or carbon.